The Acoustic Change Complex in Young Children with Hearing Loss: A Preliminary Study - Martinez, Amy S.; Eisenberg, Laurie S.; Boothroyd, Arthur (Seminars in Hearing, 2013)
The acoustic change complex (ACC) is a cortical auditory evoked potential elicited in response to a change in an ongoing sound. The ACC may have promise for assessing speech perception in infants and toddlers. In this preliminary study, the ACC was elicited in adults and young children in response to changes in speech stimuli representing vowel height /u/-/a/ and vowel place /u/-/i/ contrasts. The participants were adults with normal hearing (n = 3), children with normal hearing (n = 5), and children with mild to moderately severe bilateral sensorineural hearing loss (n = 5). The children with hearing loss were hearing aid users. The ages ranged from 2 years 3 months to 6 years 3 months for the children and 44 to 55 years for the adults. Robust P1-N1-P2 responses were present for the adults and P1-N2 responses were present for all but the youngest child with hearing loss. The ACC response for the vowel place contrast was less robust than that for the vowel height contrast in one child with substantial hearing loss. The findings from this preliminary study support the conclusion that the ACC can be used successfully to assess auditory resolution in most young children.
Keywords: Acoustic change complex; cortical evoked potentials; auditory speech perception; childhood hearing loss